Biomedical Applications of MXene‐Integrated Composites: Regenerative Medicine, Infection Therapy, Cancer Treatment, and Biosensing. (24th June 2022) - Maleki, Aziz; Ghomi, Matineh; Nikfarjam, Nasser; Akbari, Mahsa; Sharifi, Esmaeel; Shahbazi, Mohammad‐Ali; Kermanian, Mehraneh; Seyedhamzeh, Mohammed; Nazarzadeh Zare, Ehsan; Mehrali, Mehdi; Moradi, Omid; Sefat, Farshid; et al.
Abstract: MXenes (viz., transition metal carbides, carbonitrides, and nitrides) have emerged as a new subclass of 2D materials. Due to their outstanding physicochemical and biological properties, MXenes have gained much attention in the biomedical field in recent years, including drug delivery systems, regenerative medicine, and biosensing. Additionally, the incorporation of MXenes into hydrogels has garnered significant interest in biomedical engineering as an electroactive and mechanical nanoreinforcer capable of converting nonconductive scaffolds into excellent conductors of electricity with an impressive effect on mechanical properties for the engineering of electroactive organs and tissues such as cardiac, skeletal muscle, and nerve. However, many questions and problems remain unresolved that need to be answered to usher these 2D materials toward their true destiny. Thus, this review paper aims to provide an overview of the design and applications of MXene‐integrated composites for biomedical applications, including cardiac tissue engineering, wound healing, infection therapy, cancer therapy, and biosensors. Moreover, the current challenges and limitations of utilizing MXenes in vivo are highlighted and discussed, followed by its prospects as a guideline toward possible various futuristic biomedical applications. This review article will inspire researchers, who search for properties, opportunities, and challenges of using this 2D nanomaterial in biomedical applications. Abstract : Owing to the unique physicochemical and biological properties of MXenes and their nanocomposites, these platforms are employed in different sectors of biomedicine. Herein, the fabrication of MXene‐based nanoplatforms is introduced. Biomedical applications of MXene‐integrated composites in biomedicine (e.g., regenerative medicine, infection therapy, cancer treatment, and biosensor) are highlighted.